PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP KEMAMPUAN KEAKSARAAN MENGENAL HURUF ANAK USIA 5-6 TAHUN DI TK KRISTEN SILO - Viona Lulu Kore, Angry; Yuniati, Yohana; P.E Djokaho, Margareta; G. Betty, Credo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early literacy ability to recognize letters is one of the crucial developmental aspects that needs to be stimulated from an early age. This study aims to determine the effect of using Wordwall media on the literacy ability to recognize letters of children aged 5-6 years at TK Kristen Silo. This study used a quantitative experimental approach with a one group pretest-posttest design. The population consisted of 25 children at TK Kristen Silo, and purposive sampling was used to select 14 children aged 5-6 years with low letter recognition ability as the sample. Data were collected using an oral test instrument covering eight literacy indicators and analyzed using the Paired Sample T-Test with SPSS. The results showed that the mean posttest score (27.00) was significantly higher than the mean pretest score (21.86), with an increase of 5.14 points. The hypothesis test yielded t-value of 6.564 > t-table 2.160 with significance value of 0.001 < 0.05, leading to the rejection of H₀ and acceptance of Hₐ. It is concluded that the use of Wordwall media has a significant effect on improving the literacy ability to recognize letters in children aged 5-6 years at TK Kristen Silo.